Potencial alelopático de macrófitas aquáticas e a influência dos fatores ambientais na sua distribuição em um estuário cego - Takao, Leandro Kenji (Universidade Federal de São Carlos, 2010)
Tropical blind estuaries have a flooding regime that exposes the flora to extreme changes in environmental conditions. Salinity and flooding seem to be the major factors influencing vegetal species distribution in these environments. Aquatic macrophytes are one of the most productive communities and through their metabolism are able to influence aquatic ecosystem. Allelopathic interactions are among the factors that affect phytosociology and are increased under biotic and abiotic stress conditions. The allelopathic potential has been explored for its application as natural herbicide in weed species control. The aim of our study was to evaluate salinity and flooding influence on species distribution, diversity and richness. We also studied and compared allelopathic properties of aquatic macrophyte species and their possible application to inhibit weeds. For this, we studied the macrophytes´ community and its relation with abiotic variables (flooding and salinity) in Massaguaçu River tropical estuary, located in Caraguatuba-SP. We found 54 macrophyte species belonging to 27 families in this environment. The distribution of these species seems to be related to flooding regime and salinity. Species diversity and richness vary with flooding time but not with salinity. Vegetation presents a sequence of heterogeneous communities through saline gradient and flooding categories. Thereby, Massaguaçu River estuary is defined as a double ecocline: lengthwise (between freshwater and seawater) and lateral (between terrestrial and aquatic habitats). We noticed several species with allelopathic potential over lettuce, a bioindicator species, in laboratory experiments with different inhibition potentials. Then, we found significative inhibitory effects of Ipomoea cairica (L.) Sweet extracts on the germination and early development of weed species: B. pilosa, E. crusgalli, E. heterophylla e I. grandifolia. Our results help to understand tropical blind estuarine environment and its floristic compositon, characterizing their vegetable populations, distribution and potential to be explored as an alternative to synthetic herbicides.
Keywords: Ecologia; Salinidade; Alagamento; Diversidade biológica; Ecótono; Alelopatia; Diversidade e riqueza de espécies; Ecoclina; Allelopathy; Ecocline; Flooding; Salinity; Species diversity and richness; CIENCIAS BIOLOGICAS::ECOLOGIA